2015
DOI: 10.2503/hortj.mi-036
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-fertilization Barriers in Interspecific Hybridization between Evergreen Azalea Species and <i>Rhododendron uwaense</i> H. Hara & T. Yamanaka

Abstract: Reciprocal crosses between nine evergreen azalea species and Rhododendron uwaense were performed to clarify the pre-and post-fertilization barriers in this interspecific hybridization for the purpose of obtaining fragrant evergreen azaleas. Unilateral incompatibility appeared in this hybridization. When evergreen azalea species were used as a seed parent, many pollen tubes stopped elongating in a style and no seed could be obtained. The reverse crosses exhibited inhibition of pollen tube penetration into ovule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…In studies on breeding compatibility, a histological analysis can provide key clues to determine the reason for reproductive obstacles. Previous studies have shown that incompatibility reactions are caused by prevention of pollen germination, pollen tube growth arrest, or pollen tube navigation during its growth (He et al, 2019;Kacar et al, 2015;Okamoto and Ureshino, 2015;Varotto et al, 1995). In a recent study, callus tissue that developed in the stigma and style blocked the development of the pollen tube and led to incompatibility of Passiflora species (P. alata, P. cincinnata, P. edulis, P. gibertii, P. mucronata) and changed the direction of crossings (Soares et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on breeding compatibility, a histological analysis can provide key clues to determine the reason for reproductive obstacles. Previous studies have shown that incompatibility reactions are caused by prevention of pollen germination, pollen tube growth arrest, or pollen tube navigation during its growth (He et al, 2019;Kacar et al, 2015;Okamoto and Ureshino, 2015;Varotto et al, 1995). In a recent study, callus tissue that developed in the stigma and style blocked the development of the pollen tube and led to incompatibility of Passiflora species (P. alata, P. cincinnata, P. edulis, P. gibertii, P. mucronata) and changed the direction of crossings (Soares et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another well-known example is the cytoplasmic male sterility (CMS) which is a maternally inherited trait characterized by the inability of a plant to produce functional pollen (Eckardt 2006). Hybrid chlorophyll deficiency causes white-coloured cotyledons and this has been identified to occur as a result of incompatibility between the plastid genome and the nuclear genome (Ureshino et al 1999;Okamoto and Ureshino 2015).…”
Section: Hybridization For Crop Improvement In Brassicamentioning
confidence: 99%
“…Hybrid necrosis or death of young seedlings is another form of post-zygotic incompatibility which is associated with complexities in gene interaction (Potts and Dungey 2004;Okamoto and Ureshino 2015). In Arabidopsis for instance, it has been revealed that conflict between two gene variants or loci (DANGEROUS MIX 1 (DM1) and DANGEROUS MIX 2 (DM2)) may trigger defence reactions which can be detected phenotypically in hybrids as necrotic lesions on leaves and a decline in growth and fertility (Bomblies and Weigel 2007;Chae et al 2014).…”
Section: Hybridization For Crop Improvement In Brassicamentioning
confidence: 99%
“…Unilateral cross-incompatibility(UCI) is defined as asymmetric reproductive isolation, manifested by successful crosses in one direction and unsuccessful crosses in the other ( Muñoz-Sanz et al., 2020 ). Currently, UCI has been observed in banana shrub ( Xu et al., 2017 ), jacaranda tree ( Bittencourt, 2019 ), azalea ( Okamoto and Ureshino, 2015 ), etc. However, no studies have been reported on the cytological mechanism of interspecific asymmetric hybridization in the genus Camellia between Camellia oleifera and Camellia yuhsienensis.…”
Section: Introductionmentioning
confidence: 99%